2020
DOI: 10.3390/cancers12030661
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human NK Cell-Derived Exosomes: Role of DNAM1 Receptor in Exosome-Mediated Cytotoxicity against Tumor

Abstract: Despite the pivotal role of natural killer (NK) cells in defenses against tumors, their exploitation in cancer treatment is still limited due to their reduced ability to reaching tumor sites and the inhibitory effects of tumor microenvironment (TME) on their function. In this study, we have characterized the exosomes from IL2- or IL15-cultured human NK cells. Both cytokines induced comparable amounts of exosomes with similar cargo composition. Analysis of molecules contained within or exposed at the exosome su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
139
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(148 citation statements)
references
References 46 publications
9
139
0
Order By: Relevance
“…Several studies have shown expression of NK cell receptors by NK‐EVs. Expression of FasL, DNAM‐1 and NKG2D are reported in several studies, while there is low and variable expression of NKp30, NKp46 and CD16 23,24,26 . Interestingly, NK‐EVs are also reported to contain the immune checkpoint B7‐H3/CD276 25 and CD47 27 .…”
Section: Nk‐evs Are Equipped To Kill Cancer Cellsmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies have shown expression of NK cell receptors by NK‐EVs. Expression of FasL, DNAM‐1 and NKG2D are reported in several studies, while there is low and variable expression of NKp30, NKp46 and CD16 23,24,26 . Interestingly, NK‐EVs are also reported to contain the immune checkpoint B7‐H3/CD276 25 and CD47 27 .…”
Section: Nk‐evs Are Equipped To Kill Cancer Cellsmentioning
confidence: 95%
“…EVs could also be taken up via phagocytosis or receptor‐independent endocytosis or micropinocytosis 22 . In vitro, NK‐EVs are shown to be internalized within haematological cell lines, 23,24 suggesting that NK‐EVs are endocytosed rather than fused with the target cell membranes.…”
Section: Characteristics Of Extracellular Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes produced from NK cells and their apoptotic activity in tumor cells have also been studied. Exosomes obtained from IL-2-and IL-15-stimulated NK cells were detected in peripheral blood expressing the typical NK-related molecules CD16, CD69 and NKG2D which have high penetrance rates and a marked cytolytic effect on tumor sites [156]. NK-derived exosomes carrying the tumor suppressor microRNA (miR)-186 exhibit potent activity against neuroblastoma cell lines [157] and aggressive melanoma in vitro and in vivo [158], thus opening up the possibility of clinical applications using the antitumor activity of NK-derived exosomes [159].…”
Section: Exosomes Derived From Immune System-related Cells That Play mentioning
confidence: 99%
“…Inward budding of late endosomes develop into intracellular multivesicular endosomes and RNA, DNA, proteins and other small moleculars are encapsulated into exosomes during the formation of exosome [1,2]. Various types of cells such as immune cells, broblast and endothelial cells, release exosomes into the extracellular space and microenviroment, involving the tumor pathogenesis [3,4]. Recent studies reported that tumor cell-derived exosomes stimulated cancer and sarcoma cell growth, survival, metastasis, angiogenesis and chemotherapy resistance [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%